2021
DOI: 10.47815/apsr.2021.10086
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of fertility status in soils of Dima Hasao district of Assam

Abstract: Two hundred fifty geo-referenced surfaces (0-15 cm) soil samples were collected and analysed for macronutrients and micronutrients to study fertility status in soils of Dima Hasao district of Assam and their relationship with some important soil properties. Soils of the district were found to be extremely acidic to slightly acidic in reaction with a low to high organic carbon content and low in cation exchange capacity. The soil of the district indicated that the available nitrogen, phosphorus and potassium st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
3
4
0
Order By: Relevance
“…The findings were substantiated with the positive significant correlation with OC, CEC and clay content (r= 0.384**, 0.417**, 0.406**). Similar result was observed by Basumatary et al [19] in Dima Hasao district. "The available P content in different jhum cycle and the undisturbed soil increased with the increase in jhum fallow cycle.…”
Section: Primary Nutrientssupporting
confidence: 89%
See 3 more Smart Citations
“…The findings were substantiated with the positive significant correlation with OC, CEC and clay content (r= 0.384**, 0.417**, 0.406**). Similar result was observed by Basumatary et al [19] in Dima Hasao district. "The available P content in different jhum cycle and the undisturbed soil increased with the increase in jhum fallow cycle.…”
Section: Primary Nutrientssupporting
confidence: 89%
“…The higher value of exchangeable Ca and Mg in the longer jhum fallow cycle might be due to increase in soil pH and organic carbon content as compared to initial jhum fallow cycle [8,18]. Correlation study also showed that both exchangeable Ca and Mg exhibited a significant and positive correlation with pH, OC, and CEC indicating that these properties played an important role in improvement of status of exchangeable Ca and Mg in shifting cultivated areas of Dima Hasao [19] deficit status of exchangeable Ca and Mg in the soils of Dima Hasao.…”
Section: Secondary Nutrientsmentioning
confidence: 96%
See 2 more Smart Citations
“…This might be due to high clay content in the lower horizon compared to the upper horizon, which led to impeded leaching, consequently, accumulation of calcium and magnesium in the lower horizon. Similar results were reported by Narsaiah et al (2018) and Basumatary et al (2021). It was clear that Mg 2+ was present in lower amount than Ca 2+ because of the higher mobility of the former ion.…”
Section: Soil Fertilitysupporting
confidence: 88%